2018
DOI: 10.48550/arxiv.1809.10919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

K-theory and the singularity category of quotient singularities

Nebojsa Pavic,
Evgeny Shinder

Abstract: In this paper we study Schlichting's K-theory groups of the Buchweitz-Orlov singularity category D sg (X) of a quasi-projective algebraic scheme X/k with applications to Algebraic K-theory.We prove for isolated quotient singularities over an algebraically closed field of characteristic zero that K 0 (D sg (X)) is finite torsion, and that K 1 (D sg (X)) = 0. One of the main applications is that algebraic varieties with isolated quotient singularities satisfy rational Poincaré duality on the level of the Grothen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Finally, as we have already shown that π * : A i → A i is essentially surjective, it remains to show that the induced functor π * : A i ( A i ∩ Ker π * ) → A i is fully faithful; to show this we use the argument from [PS18,Lemma 2.31] which goes as follows.…”
Section: (Iii) We Have An Equalitymentioning
confidence: 99%
“…Finally, as we have already shown that π * : A i → A i is essentially surjective, it remains to show that the induced functor π * : A i ( A i ∩ Ker π * ) → A i is fully faithful; to show this we use the argument from [PS18,Lemma 2.31] which goes as follows.…”
Section: (Iii) We Have An Equalitymentioning
confidence: 99%
“…We define the following Grothendieck groups of X with supports on Z; the first two are classical, and the last two are defined and studied in [38]. We define…”
Section: Gorenstein Varieties and Algebrasmentioning
confidence: 99%
“…K sg 0 (X)) for these groups when Z = X. Essentially from definitions (see [38,Remark 1.13]) we get a canonical exact sequence…”
Section: Gorenstein Varieties and Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorenstein terminal) threefolds. Using nodal blow ups for studying derived categories can be traced back to Orlov's interpretation of the Knörrer periodicity [22] (see also [24,Proposition 1.30]).…”
Section: Introductionmentioning
confidence: 99%